Análisis de los mecanismos de transición del protocolo de internet IPv4 a IPv6 e implementación de la mejor solución para la empresa proveedora de servicios de internet T-COMP. - Serrano Barriga, Jenniffer del Carmen (2015)
INTERNET uses the TCP / IP protocol for managing data packet traffic passing through the global information network. By an IP address, computers can communicate with each other, the same that identifies both the computer and the network to which it belongs. Currently the IP version 4 protocol, which offered a targeting strategy that was scalable for a while but then there was great difficulty, depletion of IP addresses, so that the present work titration was aimed used, analyze the different mechanisms of transition from IPv4 to IPv6 and implement the best solution for the company providing Internet T-COMP and managed to meet the parameters given by the Ministry of Telecommunications through the Telecommunications Authority regarding the transition to IPv6. The constant evolution and development of technologies led the company to acquire this new protocol (IPv6), it is how the company was able to obtain the various benefits offered by it, such as: integrated security which includes authentication and encryption of information, greater number of IP addresses to hosts and intermediate nodes can operate both IPV4 and IPV6, improved the packet routing process and a more simplified management; to make the transition to IPv6 there are several mechanisms, carrying out proper investigations proceeded to use Tunneling, which is based on the content of IPv6 packets within IPv4 and sending them to an IPv4 destination node over an IPv4 network because the destination node performs extraction IPv6 packets. Therefore, with the implementation of the mechanism mentioned above in the company providing Internet T-COMP, was given an efficient improvement in the management of IP addresses, improved support for security and thus the institution offers all its customers quality service.